Synthesis of Chiral Amines via Asymmetric Hydrogen Borrowing - Wang, Kun; Xiao, Miao; Wang, Chao (Synlett, 2021)
Chiral amines have been widely used in pharmaceutical, agrochemical and fine-chemical industries. With water as the only byproduct and requiring no extra reducing reagent, the reaction of alcohols with amines via a ‘hydrogen borrowing’ pathway is a green route to prepare chiral amines. This paper gives a brief summary of progress on asymmetric amination of alcohols to produce chiral amines via the ‘hydrogen borrowing’ strategy.
Keywords: chiral amine; amination; hydrogen transfer; hydrogen borrowing; amination; amine; alcohol